Brief hypnotic intervention increases throwing accuracy - Jalene, S.; Wulf, G. (International Journal of Sports Science and Coaching, 2014)
The present study examined whether motor skill learning could be enhanced through a hypnotic intervention. The task involved throwing a tennis ball overhand at a target. Participants were assigned to either a hypnosis or control group. Both groups first completed a pre-test of 20 throws. Prior to the second block of 20 throws (post-test), the hypnosis group received a 10-minute hypnotic intervention. The theme of the hypnosis session was to focus on the target while throwing. Participants were aroused from the hypnotic state prior to the throwing task. The control group was asked to relax in the same environment for the same length of time. Control group participants were told that focusing on the target had been shown to increase accuracy. On the post-test, as well as on a retention test (20 throws), conducted 5-8 days after the post-test, the hypnosis group showed an increase in throwing accuracy relative to the pre-test and more effective performance than the control group whose performance was similar to that on the pre-test. These findings show that hypnosis can have a positive impact on motor learning. Potential mechanisms for this effect are discussed.